Smart homes no Brasil: desafios, oportunidades e políticas públicas - Neves, Thiago Thito de Paula Oliveira (2024)
Given the growing interest in technological solutions that promote energy efficiency and sustainability, the main objective of this study was to explore the challenges and opportunities in the smart home market in Brazil, focusing on the initial development of a web application prototype. This prototype may serve as a foundation for future studies aimed at analyzing the economic feasibility of converting traditional homes into smart homes in Brazil. The research was structured as an applied and exploratory study, with a qualitative approach, using a combination of systematic literature review and document research to support the development of the prototype. The initial stage prototype developed proved to be a foundational tool with the potential for future use in studies, where, through the application of technical expertise in engineering, user feedback, and other validations, it can continuously evolve to perform the necessary calculations for the required analyses and thereby contribute to the dissemination and adoption of smart technologies in Brazil. Furthermore, the study highlights the importance of effective public policies and smart governance to promote sustainable development and the expansion of smart homes in the country.